PENGEMBANGAN ALAT UKUR KEMAMPUAN PEMAHAMAN KONSEP PADA POKOK BAHASAN SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Nur Yuliany; Rahmat Hidayat; Nursalam; Suharti; Baharuddin (Al Asma: Journal of Islamic Education, 2022)
The purpose of this study is to determine the procedure for developing measuring instruments to facilitate the ability to understand concepts on the subject of SPLTV for class X students of SMAN 6 Wajo and to find out how the quality of measuring instruments is to measure the conceptual understanding ability of the SPLTV class X students of SMAN 6 Wajo. The type of research used is research and development based on Tessmer's formative research model which consists of 4 stages, namely: (1) preliminary stage, (2) self-evaluation stage¸ (3) prototyping stage (expert review, 0ne-to -one, and small group) and (4) the field test stage. The research instruments used were validation sheets, questionnaires and tests. The data analysis technique for the validation sheet used the Aiken's V validity index, while the questionnaire and test used student response analysis and item quality analysis. The results showed that (1) the process of developing a measuring instrument for the ability to understand concepts through 4 stages, namely (a) the preliminary stage, (b) the self-evaluation stage, (c) the prototyping stage, and (d) the field test stage, (2) From the test results obtained from the one-to-one measuring instrument that has been developed at the validation test stage by the expert, it meets the valid criteria with a validity coefficient value of 0.8. The results of the analysis of the responses of students by 77% met the criteria that students responded positively to the readability of the questions. The results of the analysis of the difficulty level of the questions obtained an average total score of 0.53, including in the medium category, while the results of the analysis of distinguishing power obtained an average score of 0.24, including in the sufficient category.